Perlindungan Hukum Merek Terkenal Terkait dengan Persaingan Usaha Tidak Sehat - A.A. Ngurah Bagus Bayu Prasetia; I Nyoman Putu Budiartha; Ni Made Puspa Sutari Ujianti (Jurnal Konstruksi Hukum, 2020)
With the current development, there are many well-known brands circulating in the market all over Indonesia, especially the ones that are deliberately counterfeited by business actors violating existing regulations for profit. The circulation of a well-known brand that is widely fabricated has spread to all levels of society. With the existence of various well-known brands, there will be a negative impact, such as the emergence of brand violations which is a form of unfair business competition. This study examines the regulation towards the well-known brands in Indonesia and the legal protection for well-known brands in relation to unfair business competition in Indonesia. To achieve these goals, this study was conducted using normative legal research method. Initially, the regulation of the famous brands is regulated in the Paris Convention for the Protection of Industrial Property (Paris Convention) and the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement). At this time, Indonesia has made its own regulations regarding Famous Marks and most recently the Regulations regarding famous marks are regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Preventive legal protection aims to provide a legal umbrella for entrepreneurs who have well-known brands to anticipate violations. Repressive legal protection provides the final legal umbrella for imposing sanctions on business actors who deliberately copy the famous brands that have been registered in Indonesia. Civil and criminal remedies are given when a dispute has occurred or a violation has been committed. The government should conduct socialization regarding the forms of violations. Entrepreneurs should be more creative and advertise their own brands more so that people can get clear information about well-known brands, both genuine and the counterfeited.